Streptomyces poriferorum sp. nov., a novel marine sponge-derived Actinobacteria species expressing anti-MRSA activity - Sandoval-Powers, Megan; Králová, Stanislava; Nguyen, Giang-Son; Fawwal, Dorelle V; Degnes, Kristin; Lewin, Anna Sofia; Klinkenberg, Geir; Wentzel, Alexander; Liles, Mark R (Systematic and applied microbiology, 2021)
Marine sponges represent a rich source of uncharacterized microbial diversity, and many are host to microorganisms that produce biologically active specialized metabolites. Here, a polyphasic approach was used to characterize two Actinobacteria strains, P01-B04T and P01-F02, that were isolated from the marine sponges Geodia barretti (Bowerbank, 1858) and Antho dichotoma (Esper, 1794), respectively. Phylogenetic analysis based on 16S rRNA gene sequences indicated that strains P01-B04T and P01-F02 are closely related to Streptomyces beijiangensis DSM 41794T, Streptomyces laculatispora NRRL B-24909T, and Streptomyces brevispora NRRL B-24910T. The two strains showed nearly identical 16S rRNA gene sequences (99.93%), and the average nucleotide identity (ANI) and digital DNA-DNA hybridization (dDDH) relatedness values were 99.96% and 99.6%, respectively, suggesting that these strains are affiliated with the same species. Chemotaxonomic and culture characteristics of both strains were also consistent with the genus Streptomyces, while phenotypic properties, genome-based comparisons, and phylogenomic analyses distinguished strains P01-B04T and P01-F02 from their closest phylogenetic relatives. In silico analysis predicted that the 8.9 Mb genome of P01-B04T contains at least 41 biosynthetic gene clusters (BGCs) encoding secondary metabolites, indicating that this strain could express diverse bioactive metabolites; in support of this prediction, this strain expressed antibacterial activity against Gram-positive bacteria including a clinical isolate of methicillin-resistant Staphylococcus aureus (MRSA) EAMC30. Based on these results, the marine sponge-associated isolates represent a novel species of the genus Streptomyces, for which the name Streptomyces poriferorum sp. nov. is proposed, with P01-B04T (=DSM 111306T = CCM 9048T) as the type strain.
Keywords: Animals; DNA bakterií; multigenová rodina; Porifera; RNA, Ribosomal, 16S; DNA, Bacterial; hybridizace nukleových kyselin; antibióza; methicilin rezistentní Staphylococcus aureus; zastoupení bazí; Phylogeny; Streptomyces; Base Composition; Bacterial Typing Techniques; Sequence Analysis, DNA; Nucleic Acid Hybridization; techniky typizace bakterií; zvířata; sekvenční analýza DNA; fylogeneze; RNA ribozomální 16S; Antibiosis; Methicillin-Resistant Staphylococcus aureus; Multigene Family